Main Types of Entomophages of Juice in Orchard Gardens and the Level of their Spreading - Anorboev Azimjon Raimqulovich; Jumaeva Aziza Nomonjonqizi; Turgunov Sardorbek Nomonjon o’g’li (Research Parks Publishing LLC, 2021)
This article provides information on the distribution of entomophagous juices and their species composition in intensive orchards of Andijan region. Four species of entomophages have been identified in the intensive garden. The most common species is Coccinella septempunctata L., the relatively rare Praon volucre Hal. type.